Mechanical properties of a gelatin replacer, pectin, from banana and mango peels - Mohd. Salleh, Hamzah; Jaswir, Irwandi; Zakaria, Hamida (IIUM Press, 2011)

(untitled)
An experimental design was used to slUdy the influence of pH, tempemture and time on the extraction of pectin from banana peels (Musa) and mango peels (Mungiferu indica), The yield of the extracted pcetin was measured to dctermine the optimum extraction condition. Alcohol insoluble solid (A1S) method was used for the extraction technique where ethanol was the solvent. The design of experiment WaS performed using statistical software Design Expen to know the pattern on the experiment C"Onducted. The tcmperarure, pH and time of extraction of AIS were optimiud using 2-faetorial design. Statistical analysis showed that the optimum parameters that provided the maximum pectin yields were at 4 hours. pH 2.0 and 9O"C of extraction. The pectin yields from both banana and mango peels were measured and calculated to be within the r,mge of 53 to 134 mglg aod 58 to 122 mglg respectively.